If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + -6x = -12x Solving 48 + -6x = -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 48 + -6x + 12x = -12x + 12x Combine like terms: -6x + 12x = 6x 48 + 6x = -12x + 12x Combine like terms: -12x + 12x = 0 48 + 6x = 0 Add '-48' to each side of the equation. 48 + -48 + 6x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 6x = 0 + -48 6x = 0 + -48 Combine like terms: 0 + -48 = -48 6x = -48 Divide each side by '6'. x = -8 Simplifying x = -8
| y(12x+16z)=x(12y+14z) | | 28x^2-164x=24 | | 17x-8=-25 | | -3(1-h)=-6-6n | | -1t-23=-15 | | X+5+7=11 | | -6=-24x-15 | | f(x)=ln(121sin^2x) | | y(12x+16z)=z(14x+16y) | | 2x+8x=80 | | 9y-15=-45+4y | | -2(x-8)-23=-7 | | x(12y+14z)=z(14x+16y) | | 23-x=47 | | z(14x+16y)=y(12x+16z) | | 8n-11=13+2n | | 3X^2-3X-XY+Y= | | 15+3=1513 | | x(12y+14z)=y(12x+16z) | | 7x-2=-13 | | 3(4x-7)=4x-25 | | x(12y+14z)=y(12x+16y) | | x^2+5x=110+4x | | 2(3+4x)-2=28 | | 30n^2-192=216n | | y(8x+8z)=z(10x+8y) | | x(8y+10z)=y(8x+8z) | | x(8y+10z)=y(8x+8z)andy(8x+8z) | | 3x^2-5x+6=2x^2+4x-14 | | 4=7+1+6x | | m+qn=r | | 5x^2-20x+6=0 |